The birth of modern Europe : culture and economy, 1400-1800 : essays in honor of Jan de Vries - Cruz, Laura; Mokyr, Joel, 1946- (Leiden ; Boston : Brill, 2010)
It seems undeniable that Jan de Vries has cast an indelible impression upon the field of early modern economic history. With his rejection of traditional models that left pre-industrial Europe with little to no role to play in modern development, de Vries’ work has laid claim to the rich significance of the early modern period as the birth of the contemporary West. Culminating in The Industrious Revolution: Consumer Behavior and the Household Economy 1650 to the Present (2008), his work has changed the way scholars conceptualize and study this dynamic period, as the contributors in this volume attest. Utilizing the methods and concepts pioneered by de Vries, these authors display the depth and breadth of his influence, with applications ranging from trade to architecture, from the Netherlands to China, and from the 1400s to the present day.
Publikace představuje soubor studií věnovaných přeměnám evropské společnosti mezi lety 1400–1800. Zaměřuje se na klíčové kulturní a ekonomické procesy, které formovaly vznik moderní Evropy, a zároveň vzdává poctu významnému historikovi Janu de Vriesovi.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: 15.-19. století; hospodářské dějiny; kulturní dějiny; sociální změna; modernizace; ekonomická transformace; Evropa; Nizozemsko; dějiny ekonomického myšlení; kulturně-ekonomické změny; sborníky; 15th-19th centuries; economic history; cultural history; social change; modernization; economic transformation; Europe; Netherlands